An analytical study of knowledge levels for cow breeders in some regions of AI-Gabal AI-Akhtar- libya - Alzobaidy, Dakhel Hussein; Mohammed, Mohammed A.; Daghash, Hassan A.; Milad, Ibrahim S. (Al-Mukhtar Journal of Sciences, 2007)
The main objective of this research is to study the knowledge levels of cow breeders in some regions of AI-Gabal AI-Akhtar. the population was ( 600) researched members, a simple random sample was takcn in a ratio of (20%) of each region resulted in (120) members. A questionnaire form was designed consisting of three parts, the first part concerns with some distinctive characteristics part concerns with studying the knowledge recourses on which the researched members depend on to get their intonation in this field the third part concerns with studying the knowledge levels in the fields of care, breeding, nutrition, progeny selection, veterinary care and atmospheric conditions. Percentages, frequencies, the average, standard deviation, and simple correlation coefficient were used in data analysis of this research. The results showed that (89%) of the researched members have different educational levels, also they are of medium. and low levels in all studied fields in general. There is a correlative relationship between the general knowledge level and knowledge recourses at a significant level 0.05, r= 0.204. also a positive correlative relationship between the educational level and degree of awareness by innovations, at a significant level 0.01, r= 0.0486, the researchers recommend with establishing specialized extensional programs for agricultural requirement sealers because of their role as an important knowledge resource for breeders, they also recommend with activating the role of faculty of agriculture and veterinary medicine to increase the knowledge of cow breeders and improving their practices. They as well as recommend to the importance of establishing specialized workshop between agricultural extension department and animal production in the faculty of agriculture.